Exploring the intersections of TAM and TRI models in middle school VR technology acceptance - Lin, Xiao Ping; Li, Bin Bin; Zhang, Mingshu; Yang, Zhi (Frontiers in Education, 2023)
Background In recent years, the attitudes of middle school principals toward virtual reality (VR) have received much attention from the educational technology community. As VR continues to gain popularity in education, researchers have begun to explore middle school principals’ perceptions of VR using the Technology Acceptance Model (TAM) (perceived usefulness, and perceived ease of use) and Technology Readiness Index (TRI) (optimism, innovativeness, discomfort, and insecurity) models to explore middle school principals’ perceptions of VR. This helps to reveal the influencing factors of middle school principals’ acceptance of VR, which in turn provides theoretical support and guidance for promoting the application of VR in education. Methods To explore the factors influencing the acceptance of VR by middle school principals. We searched several databases such as Google, Scopus, and Elsevier. We focused on peer-reviewed English-language publications on VR, TAM, TRI, and middle school education from 2013 to 2023. Results Through the literature review, we found that middle school principals’ intention to use VR was significantly influenced by the TAM (perceived usefulness, perceived ease of use) and TRI (optimism, innovation, discomfort, and insecurity) models. In addition, there was some degree of intersection between the dimensions of the TRI and TAM models. Conclusion VR has been widely recognized by middle school principals as an educational tool. By providing an immersive and interactive experience, VR can be effective in improving the efficiency of school operations to a great extent.